Diagnoza obcości. Brzozowskiego krytyka Sienkiewicza jako spór o polską tożsamość - Fiołek, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This essay discusses the Anti-Sienkiewicz campaign briefly. The affair happened in 1903 in the Warsaw weekly magazine “Głos”, but was written up in many Polish newspapers. Stanisław Brzozowski (1878-1911), the beginning publicist, literary critic and novelist spoke against Sienkiewicz’s famous works. Sienkiewicz’s main novels have been criticised for their conservatism and lack of social progressiveness, although they display great narrative power and contain vivid characterisations in a style full of imagery. The lack of national independence created greater reverence towards national history in 19th century Polish literature. Sienkiewicz felt a close bond with the Polish nobility. Brzozowski tried to put his own philosophy of culture and his concept of the “philosophy of labour” into practice. He spoke as am exponent of Polish modernism and socialism.